1998
DOI: 10.5380/avs.v3i1.3745
|View full text |Cite
|
Sign up to set email alerts
|

Anesthesia and Analgesia in Antarctic Fish: An Experimental Approach

Abstract: -It was studied in Antarctic fishes the anesthetic and/or analgesic actions of central depressors ketamine, fentanyl and thiopental as well as the local anesthetic benzocaine. The drugs were added to aerated marine water at temperatures of 1-1.5 C. Ketamine (15 mg/L) and fentanyl (50 g/L) failed in inducing anesthesia but caused a long lasting analgesia and sedation. Thiopental was required in doses of 100 mg/L to anesthetize the fishes, that is, about 30 times higher than the usual anesthetic dose for mammals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
0
5
0
1
Order By: Relevance
“…Unanesthetized fish suffer tremendous amount of stress during catching, transporting or when submitted to manipulation and disturbance of its natural environment. The stress and pain have crucial effects on the physiological responses and biochemical profile, inducing endocrine and metabolic disturbance in the fish (Iwama et al 1989;Bruecker and Graham 1993;Yoshikawa et al 1994;Bastos-Ramos et al 1998). Recent research studies have suggested that fish are capable of pain perception (Sneddon 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Unanesthetized fish suffer tremendous amount of stress during catching, transporting or when submitted to manipulation and disturbance of its natural environment. The stress and pain have crucial effects on the physiological responses and biochemical profile, inducing endocrine and metabolic disturbance in the fish (Iwama et al 1989;Bruecker and Graham 1993;Yoshikawa et al 1994;Bastos-Ramos et al 1998). Recent research studies have suggested that fish are capable of pain perception (Sneddon 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Ketamine in combination with fentanyl has induced anesthesia experimentally in Antarctic fish (Bastos-Ramos et al, 1998). Ketamine with xylazine will induce anesthesia in grey nurse sharks in 10-20 min for 10-20 min (Smith, 1992).…”
mentioning
confidence: 99%
“…A fourth, untreated group served as a control. The doses of ketamine and xylazine were based on preliminary experiments conducted in the common carp, as well as on the literature (Smith, 1992, Bastos-Ramos et al, 1998. We measured time to anesthesia in the fish by observing cessation of voluntary swimming and loss of responses to pinching the skin with forceps and pricking the tail with a 22-gauge needle every 2-3 min (Smith, 1992, Bastos-Ramos et al, 1998Zahl et al, 2009).…”
mentioning
confidence: 99%
See 2 more Smart Citations